Rheological Properties of Wheat Flour Modified by Plasma-Activated Water and Heat Moisture Treatment and in vitro Digestibility of Steamed Bread - Shi, Miaomiao; Cheng, Yanqiu; Wang, Fei; Ji, Xiaolong; Liu, Yanqi; Yan, Yizhe (Frontiers in Nutrition, 2022)
The study investigated the effects of plasma-activated water (PAW) and heat moisture treatment (HMT) on the rheological properties of wheat flour and the in vitro digestibility of steamed bread partially replaced by the modified wheat flour. After HMT, the gelatinization temperature of wheat flour increased and the gelatinization enthalpy reduced. The solubility and swelling power of wheat flour increased after the heat-moisture treatment. The solubility of modified flour after PAW-HMT treatment was lower than that of DW-HMT at the same temperature. The wheat flour with HMT had higher storage modulus (G') and loss modulus (G"), and had better ductility and deformability. Common wheat flour was partially replaced by modified flour to make steamed bread. The results indicated that the volume, height, diameter and specific volume of steamed bread were significantly decreased with the addition of HMT flour. However, the hardness, viscosity and chewiness increased significantly. The resistant starch content of steamed bread with the modified wheat flour increased. The results provide new insights for the development of new functional steamed bread.